'Reconstructing babel': Christian missions and knowledge production in the Middle East, nineteenth-twentieth century. Issue 2 (3rd July 2022) - Sanchez Summerer, Karène; Bourmaud, Philippe; Gabry-Thienpont, Séverine; Levant, Marie; Neveu, Norig
ABSTRACT: How was missionary knowledge received and interpreted by scholars and church historians in Europe and Russia? Many late nineteenth and early twentieth-century academics utilised knowledge production from Christian missions, notably by way of scholarly Orientalism. However, the history of this knowledge is also a history of representations: while missionary knowledge helped showcase the cultural and religious traditions of Eastern Christianity, what were the underlying motives and especially the consequences? This article examines the formulation and circulation of Eastern Christian knowledge on either side of the Mediterranean, especially on the basis of Catholic missionary archives and academic productions, the study of which is sometimes rooted in non-Anglophone academic traditions. The aim is to shed light on how knowledge relating to Eastern Christianity was assimilated in Europe, as well as the role missions played in this process, especially from the last third of the nineteenth century, when the institutions and instruments for the circulation of knowledge emerged. Another objective is to address the circulations and transformations of this knowledge on either side of the Mediterranean: collected and developed in major European libraries and universities, it was integrated by the governance structures of churches, but quite often also returned to the space it originated from, where it was reappropriated and gave rise to patrimonial processes, notably alongside the sometimes tragic experiences of certain communities during the end of the Ottoman Empire and the establishment of new states. Christian missions, at the intersection of East and West, were at the heart of this dynamic .